Garbage Management Plan in Pollution Prevention Efforts on the MV. Medelin First - R., Sulastriani; Nurmala, Eka; Jamil, T. M.; Dahlan, Harris R.; Syahid, Moh. (PT. Alpha Trianguli Australis, 2025)
In today's modern era, maritime transportation has experienced rapid progress and has a strategic role in supporting the distribution of goods between regions. The high level of pollution in the sea area due to waste that mostly comes from ships has encouraged the International Maritime Organization (IMO) to establish a number of regulations contained in Marpol 73/78 Annex V, which of course specifically regulates various problems regarding the prevention of pollution by waste through nine main provisions. Efforts to reduce the level of marine pollution caused by ship activities require understanding, skills, and also accountability from the crew on board. The study was conducted by adopting various qualitative approaches and using descriptive methods, which of course aim to explore and describe a phenomenon in detail through non-quantitative data. The results of this study are: 1) Factors that cause pollution on the MV. Medelin First: a) Cargo; b) Activities on deck; and c) Crew food; and 2) Implementation of the garbage management plan on the MV. Medelin First: a) Comprehensive socialization of the MARPOL 1973 regulations: b) Provision of clear symbols and markings on trash bins; c) Preparation and implementation of internal ship regulations; d) Imposing sanctions or direct reporting to the company if a violation occurs; e) Increasing awareness and responsibility among ship crews; and f) Encouraging effective cooperation between ship crews in implementing waste management.